Thermal analysis for ferromagnetic fluid with hybrid nano-metallic structures in the presence of Forchheirmer porous medium subjected to a magnetic dipole - Abdulmajeed Almaneea (Case Studies in Thermal Engineering, 2021)
This study is about thermal enhancement in hybrid nano-ferrofluid. The conservation equations with thermo-correlations are solved numerically and computed solutions are used for parametric study related to flow of fluid and transfer of heat energy. The convergent solutions are derived via the finite element method (FEM). A mesh-free study is performed. Flow experiences a sufficient amount of resistive force by the porous medium. It is noted that Darcy porous is less resistive than Forchheirmer porous medium. It is also noted that convective heat transfer is compromised when the Forchheirmer parameter is increased. Dissipation effects are responsible for an increase in temperature and hence, an increase in thermal boundary layer thickness is noted. It is also observed that heat dissipation in a hybrid nanofluid is stronger than that in a nanofluid. The numerical values read the wall shear stress exerted by hybrid nanofluid is greater than wall shear stress by nano-ferrofluid. The wall shear stress increases as a function of the ferro-hydrodynamic parameter. However, the wall heat transfer rate (Nusselt number) decreases as the ferro-hydrodynamic parameter is increased. Similarly, wall shear stress increases versus Curie temperature number whereas Nusselt number decreases when the porosity parameter is increased. The porous medium is responsible for more wall shear stress on the surface. The transfer of heat in the presence of a porous medium in a fluid is greater than the rate of heat transfer in fluid in the absence of a porous medium. Viscous dissipation is responsible for the increase of the rate of heat transfer.